Potent Activities of Roemerine against Candida albicans and the Underlying Mechanisms - Chaoyu Ma (Molecules, 2015)
Roemerine (RM) is an aporphine alkaloid isolated from the fresh rattan stem of Fibraurea recisa, and it has been demonstrated to have certain antifungal activity. This study aimed to investigate the antifungal activity of RM and the underlying mechanisms in Candida albicans (C. albicans). The in vitro antifungal activity of RM was evaluated by a series of experiments, including the XTT reduction assay, confocal laser scanning microscopy assay, scanning electron microscope assay. Results showed that 1 μg/mL RM inhibited biofilm formation significantly (p < 0.01) both in Spider medium and Lee’s medium. In addition, RM could inhibit yeast-to-hyphae transition of C. albicans in a dose-dependent manner. The biofilm-specific and hypha-specific genes such as YWP1, SAP5, SAP6, HWP1, ECE1 were up-regulated and EFG1 was down-regulated after 8 μg/mL RM treatment. Furthermore, the toxicity of RM was investigated using C. elegans worms, three cancer cells and one normal cell. The date showed that RM had no significant toxicity. In conclusion, RM could inhibited the formation of C. albicans biofilm in vitro, but it had no fungicidal effect on planktonic C. albicans cells, and the anti-biofilm mechanism may be related to the cAMP pathway.